Development of Learning Needs - Grounded Pedagogical Intervention Program for Adults with Social Anxiety Disorders - Gehtmane-Hofmane, Ilona; Nīmante, Dita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The cognitive behavior therapy is one of the most widely used and is considered as the most effective method of treating social anxiety. However there are some researches drawing attention to the necessity to create new, effective methods of intervention for solving of problems caused by social anxiety. For the present moment there are made various researches concerning the different aspects of the disorders caused by the social anxiety within the fields of psychology and psychosomatic medicine, but there are almost no researches within the context of social anxiety in the field of pedagogy. Therefore there is lack of pedagogical solutions for the support of people having the disorders caused by social anxiety. Therefore there is a reasoned necessity to develop a learning-needs-based program of pedagogical intervention for reduction of social anxiety. The Article reflects the results of an empirical research, allowing identifying the learning needs of adults with social anxiety disorders, which will establish the target and tasks of developing program of pedagogical intervention.